2017
DOI: 10.1177/1177180117714406
|View full text |Cite
|
Sign up to set email alerts
|

Generating and sustaining positive spaces: reflections on an Indigenous youth urban arts program

Abstract: Life in the city for any youth can be challenging without a proper support network. For Indigenous youth in particular, the unique burden of intergenerational trauma due to the residual effects of colonialism (e.g. residential schools and historical outlawing of traditional practices) can contribute to both unhealthy behaviors and a continuation of “culturally unsafe” spaces. As a response to these challenges, this article examines the positive effects that a grassroots film creation and production program in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…For the 22 research projects, a common practice was to tailor research processes to local contexts, perspectives, and norms. Several factors contributed to these efforts: the research team either had pre-established or developed new relationships with the community partner(s) prior to initiating the study and throughout the study 10 ; researchers often engaged in reflexivity, and grad students were supported/guided by a culturally competent, safe, and supportive supervisor(s) 11 ; researchers often participated in activities within the community 12 ; elders/respected community members were sought for guidance 13 ; (local) cultural protocols/methods (e.g., offering tobacco, smudging, traditional feasts, opening/closing prayers, Haudenosaunee consensus building, carrying out interviews in Anishinaabemowin, visions) were purposefully (not) incorporated into the research process, guided by Indigenous team members/knowledge holders/keepers 14 ; research teams and community partners predominately indicated that they incorporated a strengths-based approach into the project 15 ; when research teams used Western paradigms/methodologies for the research projects, they were philosophically congruent with Indigenous ways of knowing 16 ; Rand (2016), Robbins et al (2017), Ryan (2016), Vukic et al (2016), Webkamigad (2017), Wright (2019), Yap and Yu (2016), and Zehbe et al (2012) 18…”
Section: Process-related Elements Of Two-eyed Seeing Studies That Accomplished Their Objectives (Thematic Analysis)mentioning
confidence: 99%
“…For the 22 research projects, a common practice was to tailor research processes to local contexts, perspectives, and norms. Several factors contributed to these efforts: the research team either had pre-established or developed new relationships with the community partner(s) prior to initiating the study and throughout the study 10 ; researchers often engaged in reflexivity, and grad students were supported/guided by a culturally competent, safe, and supportive supervisor(s) 11 ; researchers often participated in activities within the community 12 ; elders/respected community members were sought for guidance 13 ; (local) cultural protocols/methods (e.g., offering tobacco, smudging, traditional feasts, opening/closing prayers, Haudenosaunee consensus building, carrying out interviews in Anishinaabemowin, visions) were purposefully (not) incorporated into the research process, guided by Indigenous team members/knowledge holders/keepers 14 ; research teams and community partners predominately indicated that they incorporated a strengths-based approach into the project 15 ; when research teams used Western paradigms/methodologies for the research projects, they were philosophically congruent with Indigenous ways of knowing 16 ; Rand (2016), Robbins et al (2017), Ryan (2016), Vukic et al (2016), Webkamigad (2017), Wright (2019), Yap and Yu (2016), and Zehbe et al (2012) 18…”
Section: Process-related Elements Of Two-eyed Seeing Studies That Accomplished Their Objectives (Thematic Analysis)mentioning
confidence: 99%
“…2018; Robbins et al. 2017). Other research has suggested that drama and theater‐based interventions can involve psychotherapeutic processes that enable individuals to gain insight and promote the resolution of social‐integration issues, such as problems relating to others, difficulties with communication, problems with understanding the meaning of their behavior, and difficulties with self‐confidence (Emunah 1990; Smeijsters and Cleven 2006; Walsh 1990).…”
Section: Youth Performance Theater and Health Outcomesmentioning
confidence: 99%
“…2018; Robbins et al. 2017). Indeed, several authors write that dramatic play and role play exercises are especially useful for young people who are actively experimenting with the question “Who am I?” by allowing them to try out different roles and perspectives (Hughes and Wilson 2004; Ritenburg et al.…”
Section: “Opening Up” and Rehearsing Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Employing arts-based methodologies with Indigenous youth reflects processes of Indigenization and decolonization while also providing access to emotional and spiritual engagement, personal expression, and self-driven learning (Big-Canoe & Richmond, 2014; Wahbe et al, 2007). The efficacy of arts-based research initiatives is increasingly well documented (Archibald & Dewar, 2011; Fanian, Young, Mantla, Daniels, & Chatwood, 2015; Flicker et al, 2014; Robbins, Linds, Ironstand, & Goodpipe, 2017). Indigenous youth, in particular, blend the traditional and the contemporary to express Indigeneity in new and innovative ways.…”
Section: Arts-based Approaches To Researchmentioning
confidence: 99%